Analysis of the Influence of Communication on Employee Performance Satisfaction with Supervision as a Mediating Variable at Private Contractor Company (International Journal of Scientific Research and Management (IJSRM), 2021)
Private project worker organization in Medan declined as of late. Decrease in Representative Fulfillment is brought about by a few things; diminished nature of correspondence and management. The examination tests were drawn by utilizing the immersion recipe comprising of 70 representatives. The halfway testing showed that correspondence has a positive and huge impact on representative fulfillment, wherein the T-count is 4.392 and the worth of T-table is 1.66691, then, at that point, the worth of T-count> T-table (4.392> 1.66691) with huge worth of 0,000> 0.05. The incomplete testing showed that management has a positive and huge impact on worker work fulfillment, in which the worth of oversight variable T-count 2.015> T-table 1.66691 with an importance worth of 0.005> 0.05. All the while, correspondence and management have a positive and critical impact on worker work fulfillment up to 15,467 in which F-table is 2.74.